The forgotten genocide - Courtois, Sébastien de, 1974- (Piscataway, NJ)
xxi, 373 sayfa, [9] sayfa resim
Keywords: “The first and only extensive treatment of the genocide of the Aramaic-speaking Christians of the Middle East, in particular the Syriac Orthodox communities, in the late 1800s and early 1900s under the Ottomans. Courtois bases his study on the diplomatic archives of the French Foreign Affairs office (Quai d'Orsay), the archives of the Dominican Mission at Mosul, Iraq, written eyewitness accounts, and oral interviews with genocide survivors conducted by the author“ -- Yayıncı.